Reprogramming efficiency and pluripotency of mule iPSCs over its parents†. - Zhang, Jia; Zhao, Lixia; Fu, Yuting; Liu, Fangyuan; Wang, Zixin; Li, Yunxia; Zhao, Gaoping; Sun, Wei; Wu, Baojiang; Song, Yongli; Li, Shaohua; Hao, Chunxia; et al. (Oxford University Press (OUP), 2023)
The mule is the interspecific hybrid of horse and donkey and has hybrid vigor in muscular endurance, disease resistance, and longevity over its parents. Here, we examined adult fibroblasts of mule (MAFs) compared with the cells from their parents (donkey adult fibroblasts and horse adult fibroblasts) (each species has repeated three independent individuals) in proliferation, apoptosis, and glycolysis and found significant differences. We subsequently derived mule, donkey, and horse doxycycline (Dox)-independent induced pluripotent stem cells (miPSCs, diPSCs, and hiPSCs) from three independent individuals of each species and found that the reprogramming efficiency of MAFs was significantly higher than that of cells of donkey and horse. miPSCs, diPSCs, and hiPSCs all expressed the high levels of crucial endogenous pluripotency genes such as POU class 5 homeobox 1 (POU5F1, OCT4), SRY-box 2 (SOX2), and Nanog homeobox (NANOG) and propagated robustly in single-cell passaging. miPSCs exhibited faster proliferation and higher pluripotency and differentiation than diPSCs and hiPSCs, which were reflected in co-cultures and separate-cultures, teratoma formation, and chimera contribution. The establishment of miPSCs provides a unique research material for the investigation of "heterosis" and perhaps is more significant to study hybrid gamete formation.
Keywords: donkey; horse; iPSCs; mule; pluripotency; Horses; Animals; Induced Pluripotent Stem Cells; Cellular Reprogramming; Equidae; Cells, Cultured; Cell Differentiation; Fibroblasts; Octamer Transcription Factor-3